Exclusive breastfeeding practice during first six months of an infant's life in Bangladesh: a country based cross-sectional study - Murad Hossain; Ashraful Islam; Tunku Kamarul; Golam Hossain (BMC, 2018)
Abstract Background Breastfeeding offers incredible health benefits to both child and mother. It is suggested by World Health Organization that an able mother should practice and maintain exclusive breastfeeding for first six months of her infant's life. The objective of this study was to determine the prevalence and factors associated with exclusive breastfeeding for first six months of an infant's life in Bangladesh. Methods Data was extracted from Bangladesh Demographic and Health Survey (BDHS-2014). BDHS-2014 collected data from 17,863 Bangladeshi married women in reproductive age from the entire country using two stages stratified cluster sampling. We included only mothers having at least one child currently aged not less than 6 months. Mothers who did not have child to breastfeed, some incomplete information and missing samples were excluded from the data set and consequently 3541 mothers were considered in the present study. Chi-square test, binary logistic regression models were used in this study. Results The prevalence of exclusive breastfeeding (EBF) for first six months of an infant's life in Bangladesh was 35.90%. Binary multivariable logistic regression model demonstrated that relatively less educated mothers were more likely to exclusively breastfeed their children than higher educated mothers. (AOR = 2.28, 95% CI: 1.05-4.93; p < 0.05). Housewife mothers were more likely to be EBF than their counterparts (AOR = 1.20, 95% CI: 1.02-1.42; p < 0.05). Higher rate of EBF was especially found among mothers who were living in Sylhet division, within 35-49 years old, and had access to mass media, had more than 4 children, had delivered at home and non-caesarean delivery, took breastfeeding counseling, antenatal and postnatal cares. Conclusions Stepwise regression model exhibited that most of the important predictors were modifiable factors for exclusive breastfeeding. Authorities should provide basic education on EBF to educated mothers, and organize more general campaign on EBF.